एमएलए नवौँ संस्करण प्रावधानहरू: उद्धरण र सन्दर्भ - Ghodasaini, Khagendra (Haimaprabha, 2026)
This article identifies and explores the provisions incorporated into the ninth edition of the Modern Language Association (MLA) style. It provides detailed information regarding the 9th edition of the MLA formatting style used in academic research. Prevailing particularly in disciplines such as humanities, language, and literature, this style aims to bring clarity, consistency, and a scientific approach to citation and reference management. Evolving since 1944, the 9th edition of the MLA handbook was published in 2021, revised to meet the new demands of the digital era. It introduces a flexible framework for constructing a works-cited list based on the core elements of author, title, and container/source. By comparing the 9th edition with older editions, this paper explains the latest improvements implemented in academic research. In a context where navigating English documentation styles can be challenging for Nepali-speaking researchers, this article is expected to help them understand the essence and application of the MLA style directly in the Nepali language. Utilizing examples, explanations, and qualitative research methods, the fundamental aspects of this style are presented in a simple yet clear manner, alongside various examples of in-text citations and referencing formats. Overall, the MLA 9th edition stands as a useful, flexible, and user-friendly style for researchers to maintain uniformity, transparency, and accuracy in writing, the effective use of which increases the potential of connecting the Nepali research tradition with international standards.